2022
DOI: 10.3390/ma15051799
|View full text |Cite|
|
Sign up to set email alerts
|

Silver and Gold Nanoparticles for Antimicrobial Purposes against Multi-Drug Resistance Bacteria

Abstract: Several pieces of research have been done on transition metal nanoparticles and their nanocomplexes as research on their physical and chemical properties and their relationship to biological features are of great importance. Among all their biological properties, the antibacterial and antimicrobial are especially important due to their high use for human needs. In this article, we will discuss the different synthesis and modification methods of silver (Ag) and gold (Au) nanoparticles and their physicochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 192 publications
(190 reference statements)
3
42
0
2
Order By: Relevance
“…Indeed, the silver nanoparticles developed in the unfiltered external solution of the cyanobacterial cultures showed indications of many functional groups including peptides as indicated from the functional group bands detected in the FTIR spectroscopy. With regard to the gold nanoparticles, it is suggested that they owe their antimicrobial activity in part to their electrical and optical properties (Rabiee et al, 2022). the antimicrobial superiority of silver nanoparticles over that of gold nanoparticles is mainly attributable to release of silver ions from those nanoparticles unlike gold nanoparticles.…”
Section: The Antibacterial Bioassaymentioning
confidence: 99%
“…Indeed, the silver nanoparticles developed in the unfiltered external solution of the cyanobacterial cultures showed indications of many functional groups including peptides as indicated from the functional group bands detected in the FTIR spectroscopy. With regard to the gold nanoparticles, it is suggested that they owe their antimicrobial activity in part to their electrical and optical properties (Rabiee et al, 2022). the antimicrobial superiority of silver nanoparticles over that of gold nanoparticles is mainly attributable to release of silver ions from those nanoparticles unlike gold nanoparticles.…”
Section: The Antibacterial Bioassaymentioning
confidence: 99%
“…The catalytic activity of nanogold-composite was investigated using PCTM in the presence of H 2 O 2 without and with light irradiation. H 2 O 2 served as a source of •OH radicals for PCTM oxidation, and irradiation would enable the photocatalytic activity of the Au NPs (Rabiee et al 2022).…”
Section: Paracetamol Removal Kineticsmentioning
confidence: 99%
“…Therefore, nanomaterials can be an excellent toolkit for the development of various treatment strategies using different nanoplatforms against multi-drug resistant (MDR) biofilm and planktonic infections. 21 Accordingly, there is an urgent need to discuss the various nanomaterial-based therapies available for preventing AMR and biofilm-related chronic infections, delaying wound healing and ischemic (poor blood flow) disorders, and ultimately preventing limb amputations.…”
Section: Introductionmentioning
confidence: 99%